Print, authority, and the bills of mortality in seventeenth-century London. Issue 6 (2nd November 2021) - Murel, Jacob
ABSTRACT: The bills of mortality, published by London's Company of Parish Clerks during the seventeenth century, provided Londoners with epidemiological data to track the plague's weekly and yearly development throughout London's neighborhoods. Past scholars have argued that, while the printed bills of mortality were regarded as official and reliable documents, the elderly women parish searchers responsible for compiling the bills' data were deemed untrustworthy. By contrast, the present essay proposes that this claim is only half true, arguing instead that Londoners maligned the elderly women searchers as a means of discrediting the printed bills of mortality. As with many printed documents in early modern England, the bills were not universally trusted and, moreover, were often co-opted by political dissenters to oppose London's ruling authorities and their public health measures. This essay ultimately argues that the Company of Parish Clerks published their official compilation of bills known as London's Remembrancer during a time of political strife in an effort to quell social disorder and assert the credibility of their printed bills of mortality against dissenting writers and pirated copies. Drawing from Adrian Johns' previous work covering the Royal Society's methods for establishing the credibility and authority printed works, this essay demonstrates how the London's Remembrancer employs similar strategies previously outlined by Johns in order to assert the reliability and authority of the Company of Parish Clerks' bills of mortality.